Signals from the Fourth Dimension Regulate Drug Relapse. Issue 7 (July 2016) - Mulholland, Patrick J.; Chandler, L. Judson; Kalivas, Peter W.
Abstract : Despite the enormous societal burden of alcohol and drug addiction and abundant research describing drug-induced maladaptive synaptic plasticity, there are few effective strategies for treating substance use disorders. Recent awareness that synaptic plasticity involves astroglia and the extracellular matrix is revealing new possibilities for understanding and treating addiction. We first review constitutive corticostriatal adaptations that are elicited by and shared between all abused drugs from the perspective of tetrapartite synapses, and integrate recent discoveries regarding cell type-specificity in striatal neurons. Next, we describe recent discoveries that drug-seeking is associated with transient synaptic plasticity that requires all four synaptic elements and is shared across drug classes. Finally, we prognosticate how considering tetrapartite synapses can provide new treatment strategies for addiction. Trends: Drug-induced plasticity involves all aspects of tetrapartite synapses. Relapse involves common mechanisms that span multiple classes of abused drugs. Tetrapartite synapses are novel targets for treating addiction.